Description on some rescued turtles and their translocation at Turtle Rescue and Conservation Centre (TRCC), Sanischare, Jhapa - Kharel, Milan; Chhetry, Damodar Thapa (BIBECHANA, 2014)
The present paper deals with the brief introduction of Turtle Rescue and Conservation Centre (TRCC) and description of some rescued turtles. Nine specimens of turtles belonging to five genera were rescued and translocated to the centre till date including 9.3 kg male Indian Peacock soft-shelled turtle (Nilssonia hurum) for the first time from Jhapa district. The rescue operations were conducted for the translocation of turtles confiscated from the local market, censorial collectors, fisherman and public residence. The high resolution photographs of captured specimens, their necessary biometry and GPS coordinates of location were taken. Species identification was done with the help of and pictorial field guide and relevant literatures. Climatic data of study area were recorded from Gainde Irrigation Project, Maidhar, Jhapa. Interviews were taken during field visits with the help of structured questionnaire. Preliminary rescue data showed that the Indian flap-shelled turtle (Lissemys punctata) and Yellow bellied roofed turtle (Pangshura flaviventer) were the most overexploited species in the vicinities of the study area. The climatic condition of the rescue centre and water quality found suitable to support terrestrial and freshwater turtles and other various wetland flora and fauna. However, the rapid population growth and habitat destruction due to deforestation, unmanaged urbanization and expansion of agricultural land are found as the major threats to the survival of turtles and other wetland creatures at the study area and its vicinities. DOI: http://dx.doi.org/10.3126/bibechana.v11i0.10394 BIBECHANA 11(1) (2014) 141-148